Motivation as part of prevention of cardiovascular diseases as seen by citizens of the Czech Republic - Olišarová, Věra; null, null; Tóthová, Valérie; Chloubová, Iva; Adámková, Věra (STEF92 Technology Ltd., 2017)
Background: Cardiovascular diseases constitute one of the main causes of deaths in Europe. They also rank among the most frequent causes of disability. That leads to high economic burden. The occurrence of those diseases is strongly related with life style and risk factors. Influencing of these factors in ill patients within secondary prevention and in risk factors within primary prevention will significantly reduce morbidity and mortality. Motivation is essential in the process of influencing of risk factors. It works as a factor that represents internal and external incentives related to assumption of responsibility for own health and as a factor related to perseverance in the effort to maintain the required change. Methods: The article is based on the data acquired within the "Intervention procedures in preventive cardiology" grant project. To map the implemented educational activities and the health condition, the citizens of the Czech Republic (N = 1992) were investigated with the help of a combination of a non-standardized questionnaire with the standardized SF-36 questionnaire. The actual field investigation took place from April 1-20, 2016 and was implemented all over the Czech Republic through an interviewer network. The data were analyzed under use of the SASD 1.4.12 program. Both the first and the second degree of sorting was used. The degree of dependence of selected characteristics was established based on the Chi-square goodness of fit test, T-test. Results: The analysis of the citizens’ answers shows that the physicians and the nurses motivate them to make a change in the area of nutrition most frequently. The physicians and the nurses deal with the issue of stopping smoking the least frequently. The citizens also give the best evaluation to the physicians’ and nurses’ actions in the area of life style change. On the contrary, the citizens give the worst evaluation to the motivation to change the area of exercise and stopping smoking. Conclusions: The data analysis demonstrated that the motivation by the physicians and nurses to influence the citizens’ risk factors is not sufficient. Although the motivation is necessary to achieve lasting changes, a significant percentage of the respondents reported that the physicians and nurses deal with it in individual areas only sometimes, rarely or never. The evaluation of such actions by the citizens correlates with the above stated results. The findings can constitute a feedback for the physicians and nurses, containing a challenge and motivation for implementation of changes.
Keywords: motivation; prevention; nurse; cardiovascular diseases